Em luto e luta: construindo a memória da FEB - Ribeiro, Patrícia da Silva (2013)
This thesis aims at the investigation of how the issue of conflicting memories about the participation of the Brazilian Expeditionary Force (BEF) during World War II is configured today . To accomplish this goal, it was necessary to take into account not only the political players that act in this process – among others: State, Army, Veteran's Associations and society – as well as the fluctuations and appropriations of their memory. Traumatic memories of the veterans about this event arise through different ways of self-writing – with special emphasis on journals, letters and interviews – and lead to the notion of the duty of memory in the fight for reparation and recognition.